2013
DOI: 10.1016/j.ecresq.2013.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Head Start and children's nutrition, weight, and health care receipt

Abstract: Using a sample of low-income children from the Early Childhood Longitudinal Study-Birth Cohort (N ≈ 4,350) and propensity-score weighted regressions, we analyzed children's nutrition, weight, and health care receipt at kindergarten entry, comparing 1) Head Start participants and all non-participants, and 2) Head Start participants and children in prekindergarten, other center-based care, other non-parental care, or only parental care. Overall, we found that compared to all non-participants, Head Start particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…After de-duplication, 18,793 articles underwent title/abstract screening, and the full texts of 175 articles were reviewed. Thirteen studies [40,41,42,43,44,45,46,47,48,49,50,51,52] met all of the eligibility criteria, and were included in the review. Of these, eight studies reported on diet [40,46,47,48,49,50,51,52], three reported on physical activity [40,42,45], three on sedentary behaviour [42,43,44], and one on sleep [41] outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After de-duplication, 18,793 articles underwent title/abstract screening, and the full texts of 175 articles were reviewed. Thirteen studies [40,41,42,43,44,45,46,47,48,49,50,51,52] met all of the eligibility criteria, and were included in the review. Of these, eight studies reported on diet [40,46,47,48,49,50,51,52], three reported on physical activity [40,42,45], three on sedentary behaviour [42,43,44], and one on sleep [41] outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Most included studies were from high-income countries, with seven originating from the United States [40,41,43,44], one from Australia [42], one from New Zealand [45], and one from the United Kingdom (UK) [49]. Samples were generally balanced with relation to children’s gender (although three studies did not report gender composition of the sample) [48,49,52], but varied greatly both in size (between 34 and 18,050 subjects) and ethnic composition (between 0% and 87% white, with one study not reporting race/ethnicity or country of birth [42], and five providing information only for country of birth) [46,47,49,50,52].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…45 Head Start also offers nutrition education to parents. 45,46 The children in this study had graduated out of Head Start by Time 2 and any effects that could relate to Head Start would be residual. However, the children could still have received free or reduced-cost breakfast and/or lunch at their current schools.…”
Section: Discussionmentioning
confidence: 97%